Influence of environmental conditions to α-glucosidase inhibitory activity of Caimito (Chrysophyllum cainito) leaves - Badong, Ronnie Antonio G.; Rivera, Michael John C.; Rubio, Vivente Paolo A. II (2017)
This study can be used as a reference for characterization of C. cainito leaves with respect to their phytochemical profile and determine when and where the ideal season of collection is. This study aims to evaluate the influence of location and/or season of collection of C. cainito leaves on the TLC profile and its alpha-glucosidase inhibitory property. The samples were collected from 6 regions of the Philippines: Region II, Region III, Region IV, NCR, Region VII and Region IX in the months of November 2016 and March 2017. The samples were extracted and partitioned separately using modified Kupchan partitioning. Only the ethyl acetate fraction was used in the test for phytochemicals specifically for anthraquinones, tannins and phenolic glycoside, of the three only the ferric chloride test for the presence of phenolic glycosides and tannins had a positive result. TLC was performed on the ethyl acetate fractions of all the samples including the anthraquinone standard. The results suggest that C. cainito leaves from the six different regions and two different seasons of harvest have the same chromatographic profile. Anthraquinones are also observed to be present in all of the sample excluding the obscured spots in Regions NCR and VII from the dry season. The ethyl acetate fraction of each sample was evaporated to dryness, dissolved in methanol and was tested for their inhibitory property in three different concentrations (30 μg/mL, 70 μg/mL, 150 μg/mL) in a 96-well plate bioassay. The results of the bioassay suggest that the location and/or season of collection do not affect the inhibitory property of C. cainito leaves.